Sad mood induction has an opposite effect on amygdala response to emotional stimuli in euthymic patients with bipolar disorder and healthy controls - Horacek, Jiri; Mikolas, Pavol; Tintera, Jaroslav; Novak, Tomas; Palenicek, Tomas; Brunovsky, Martin; Höschl, Cyril; Alda, Martin (Journal of psychiatry & neuroscience, 2015)
BACKGROUND: Aberrant amygdala reactivity to affective stimuli represents a candidate factor predisposing patients with bipolar disorder (BD) to relapse, but it is unclear to what extent amygdala reactivity is state-dependent. We evaluated the modulatory influence of mood on amygdala reactivity and functional connectivity in patients with remitted BD and healthy controls. METHODS: Amygdala response to sad versus neutral faces was investigated using fMRI during periods of normal and sad mood induced by autobiographical scripts. We assessed the functional connectivity of the amygdala to characterize the influence of mood state on the network responsible for the amygdala response. RESULTS: We included 20 patients with remitted BD and 20 controls in our study. The sad and normal mood exerted opposite effects on the amygdala response to emotional faces in patients compared with controls (F1,38 = 5.85, p = 0.020). Sad mood amplified the amygdala response to sad facial stimuli in controls but attenuated the amygdala response in patients. The groups differed in functional connectivity between the amygdala and the inferior prefrontal gyrus (p ≤ 0.05, family-wise error-corrected) of ventrolateral prefrontal cortex (vlPFC) corresponding to Brodmann area 47. The sad mood challenge increased connectivity during the period of processing sad faces in patients but decreased connectivity in controls. LIMITATIONS: Limitations to our study included long-term medication use in the patient group and the fact that we mapped only depressive (not manic) reactivity. CONCLUSION: Our results support the role of the amygdala-vlPFC as the system of dysfunctional contextual affective processing in patients with BD. Opposite amygdala reactivity unmasked by the mood challenge paradigm could represent a trait marker of altered mood regulation in patients with BD.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; Humans; mapování mozku; výraz obličeje; obličej; Emotions; Female; dospělí; zraková percepce; lidé; Photic Stimulation; Visual Perception; světelná stimulace; amygdala; bipolární porucha; Adult; nervové dráhy; Brain Mapping; ženské pohlaví; Neural Pathways; Male; Amygdala; Bipolar Disorder; emoce; Face; mužské pohlaví; Facial Expression